A obra para violão de Pedro Cameron: características idiomáticas e estilísticas - Perotto, Leonardo Luigi (2007)
The proposal of this research is to investigate the process of creation of the Brazilian composer Pedro Cameron, mainly through the survey and analysis of his work, pointing out specific stylistic characteristics, his perception of the classical guitar idiomatism, and its influence on compositional solutions. In the beginning of the twentieth century, there was a significant growth in the number of works written for the classical guitar by composers of diverse musical backgrounds. These works consolidated a more reorganization both in the writing and the idiomatic absorption of the instrument. The musical works for classical guitar by Pedro Cameron is part of this context, creating an important investigative link for the Brazilian contemporary repertoire. The first part of this master thesis contextualizes this moment, presenting information about the classical guitar in Brazil and the world, and a brief biography of the composer. The second part presents an analytical inquiry of some Cameron's pieces, encompassing the period between the decade of 1970 and the present days. The theoretical framework is based on authors such as Spencer & Temko (1988), Hanslick (1992), Dudeque (1996), Schoenberg (1996), Oliveira (1998), Menezes (2002) e Zuben (2004). The last part evaluates the procedures of the composer through what was observed in the analyses, presenting compositional solutions and techniques he creatively used to incorporate significant elements of the classical guitar idiomatism, influencing the process of writing and his compositional style.